Impact of Perioperative Absolute Neutrophil Count on Central Line-Associated Bloodstream Infection in Children With Acute Lymphoblastic and Myeloid Leukemia - Martynov, Illya; Schoenberger, Joachim (Frontiers in Oncology, 2021)
Background There is lack of evidence concerning safety of placement of tunnelled central venous catheter (TCVCs) in neutropenic children with acute leukemias. Here, we evaluate the impact of absolute neutrophil count (ANC) at the time of TCVC placement on development of central-line associated blood stream infections (CLABSI) in children with lymphoblastic (ALL) or myeloid leukemia (AML). Materials and methods A retrospective observational study of children undergoing TCVC placement at a tertiary referral hospital between 01/2000 and 12/2019 was performed. Traditional and competing-risks regression models were used to estimate the effect of perioperative ANC on development of CLABSI. Results 350 children (median age 6.4 [IQR: 3.1 – 10.9] years) underwent 498 consecutive TCVC implantations in neutropenic (n=172, 34.5%) and non-neutropenic conditions (n=326, 65.5%). The median length of observation per TCVC was 217.1 (IQR: 116.1 – 260.5) days with a total of 99,681 cdr. There were no differences in early (within first 30 days after TCVC placement) and overall CLABSI rates between neutropenic and non-neutropenic patients (HR 1.250, p = 0.502; HR 1.633, p = 0.143). We identified female sex (HR 2.640, p = 0.006) and the use of TCVC for treatment of relapsed leukemia (HR 4.347, p < 0.0001) as risk factors for early CLABSI and the use of double- lumen catheters (HR 2.607, p = 0.003) and use of TCVCs during leukemia relapse (HR 2.004, p = 0.005) for overall study period. Conclusion The placement of TCVC in children with neutropenia undergoing anticancer therapy for acute leukemia is safe and not associated with an elevated rate of CLABSI.